2008
DOI: 10.1021/es0871457
|View full text |Cite
|
Sign up to set email alerts
|

Global Stressors on Water Quality and Quantity

Abstract: Growing population and wealth will impact sustainability, technology selection, and governance strategies related to water issues. JULIE BETH ZIMMERMAN YALE UNIVERSITY JAMES R. MIHELCIC MICHIGAN TECHNOLOGICAL UNIVERSITY JAMES SMITH UNIVERSITY OF VIRGINIAThis inequality is especially critical for Asia, which has 60% of the world's population but only 36% of the world's water. Water quality in terms of pollutant loading also is not distributed equally and is related to the type of use and a country's level of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(95 citation statements)
references
References 17 publications
0
94
0
1
Order By: Relevance
“…Due to the water scarcity, increasing attention has been focused on the reuse of reclaimed urban wastewater for agricultural purposes since around 70% of freshwater is currently used for crop irrigation (Zimmerman et al 2008). However, application of wastewater in agriculture may pose potential risks to the environment, as wastewater treatment plants have a limited capacity to remove organic chemicals (Bueno et al 2012).…”
mentioning
confidence: 99%
“…Due to the water scarcity, increasing attention has been focused on the reuse of reclaimed urban wastewater for agricultural purposes since around 70% of freshwater is currently used for crop irrigation (Zimmerman et al 2008). However, application of wastewater in agriculture may pose potential risks to the environment, as wastewater treatment plants have a limited capacity to remove organic chemicals (Bueno et al 2012).…”
mentioning
confidence: 99%
“…Previous studies have suggested that the conventional approaches to wastewater management are not the most economical or ecologically sensitive options both generally (Daigger 2009;Zimmerman et al 2008) and in developing country contexts (Engin and Demir 2006;Massoud et al 2009). Parkinson and Taylor (2003) propose theoretically the use of decentralized wastewater in urban and peri-urban contexts in South Asia.…”
Section: Wastewatermentioning
confidence: 99%
“…A generalization trend exists within the international community suggesting that water in developing countries is of poor quality (e.g., Zimmerman et al 2008). Thereby, despite remarkable progress in environmental instrumental analytical chemistry, the water quality is rarely determined.…”
Section: A Priori Polluted Watermentioning
confidence: 99%